Myeloperoxidase and calprotectin; Any role as non-invasive markers for the prediction of ınflammation and fibrosis in non-alcoholic steatohepatitis? - Bıçakçı, Ercan; Demirtaş, Coşkun Özer; Çelikel, Çiğdem; Haklar, Goncagül; Duman, Deniz Güney (Turkish Journal of Gastroenterology, 2020)
Background/Aims: Specific serum markers reflecting hepatic inflammation and fibrosis are required to tailor the treatment strategies in non-alcoholic steatohepatitis (NASH). We aimed to investigate the roles of myeloperoxidase (MPO) and calprotectin in predicting the hepatic inflammation status and disease severity in NASH. Materials and Methods: A total of 48 patients with biopsy-proven NASH and 25 healthy volunteers with normal weight were prospectively enrolled. Serum MPO and calprotectin levels were compared between the NASH and control groups. Hepatic MPO and calprotectin expressions were compared in terms of histologic non-alcoholic fatty liver disease activity scores (NAS) (low NAS [≤4] vs. high NAS [>5]) and fibrosis stage (insignificant [F0–1]/significant [F2–4]). Results: Serum MPO and calprotectin levels were not significantly different between the NASH and control groups. In the subgroup analysis, hepatic MPO expression was significantly increased in patients with NASH with significant fibrosis than in those with insignificant fibrosis (F2–4: 7.04±3.61 vs. F0–1: 4.83±2.42, p=0.01). We found no difference between the groups with low and high NAS with regard to serum MPO and calprotectin levels and hepatic MPO and calprotectin expressions. Conclusion: This study demonstrated that hepatic MPO expression can reflect advanced fibrosis in NASH. However, when serum MPO and calprotectin levels were evaluated as potential serum markers, both did not associate with hepatic inflammation status and fibrosis stage in NASH. Therefore, our study results preclude their use as serum markers for hepatic inflammation in NASH.